Learning to Perform Narrative Task: A Semester Long Study of Task Sequencing Effects - Lambert, Craig; Robinson, Peter (2014)
This classroom-based study investigated the development of learners’ ability to summarize short stories in English in a way that requires them "to attribute intentions and mental states to others and reason from this to a conclusion about why others performed certain actions"(Robinson, 2010: 253). Two groups of 30 second-year Japanese English majors completed a similar reading and discussion course. In both of the sections, learners were acquainted with the task and goals, and provided with the same amount of reading, discussion and task performance opportunities. However, in one group, instruction followed the SSARC model of task sequencing (Robinson, 2010), whereas in the other group learners were left to their own devices in using the classroom activities to reach the task performance goal in their own ways. Written pre-test and post-test scores were compared between and within groups to determine whether and to what extent learning outcomes varied. Although findings showed that the SSARC group demonstrated a consistently higher rate of gain over the course of instruction, and felt the course to be better suited to their level of ability, there were no statistically significant differences between the two groups on measures of the syntactic complexity, intentional reasoning or grammatical accuracy of story summaries following the respective courses of instruction.